STRATEGI KOMUNIKASI DALAM PENINGKATAN KUALITAS PENYIAR DI LPPL RADIO KHARISMA 95,6 FM BENGKULU UTARA - Rasman; Renti Putri; Eti Efrina; Mukhlizar (JOISCOM (Journal of Islamic Communication), 2025)
Mass media play an essential role in modern society, with radio remaining relevant even in the digital era. LPPL Radio Kharisma 95.6 FM Bengkulu Utara, as a local public broadcasting institution, continuously strives to enhance its broadcast quality by improving the competence of its broadcasters. This study aims to analyze the communication strategies applied to enhance broadcasters' quality at Radio Kharisma. The research employed a qualitative descriptive approach through observation, interviews, and documentation techniques. The results reveal that Radio Kharisma implements communication strategies involving selective recruitment, regular training, periodic evaluations, motivational programs, and intensive interpersonal communication between management and broadcasters. These strategies have proven effective in improving broadcaster professionalism, maintaining the radio's relevance, and strengthening audience engagement. This study contributes to the development of human resource management in the field of local radio broadcasting. Keywords: Communication strategy, radio broadcaster, LPPL Radio Kharisma, quality improvement, mass media.